Earnings-Dependent Parental Leave Benefit and Fertility: Evidence from Germany - Kamila Cygan-Rehm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper examines the effects of a major change in German parental transfer system on fertility. I use the largely unanticipated reform of 2007 as a natural experiment to assess how an earnings-dependent parental leave benefit effects higher-order fertility. Given the recent introduction, this paper evaluates short-run responses by using data from the German Microcensus 2010. I find that the reform reduced the probability of having a further child in the first three years after birth. However, this effect is mainly driven by mothers on the lower bound of the benefit. Among mothers above the lower bound, short-run fertility responses are less pronounced and vary with potential earnings. The heterogeneity is in line with the structure of economic incentives.
Keywords: J13; J18; K36; 330